Foliar application of nano NPK fertilizer improves physiological activities and essential oil production in Coleus aromaticus Benth. (Ajwain Patta) - Sufina Akhter; Sana; Tariq Aftab; M. Masroor A. Khan; M. Naeem (Plant Nano Biology)
Coleus aromaticus Benth. (commonly known as Ajwain Patta) is an important aromatic plant valued for its essential oils, which possess notable therapeutic properties and substantial commercial relevance in the food and cosmetic industries. The present study evaluates the foliar application of Nano NPK fertilizer (nitrogen, phosphorus, and potassium 19:19:19) and its efficacy in improving the agronomic performance of C. aromaticus. Three concentrations (2, 4, and 6 g L−1) of Nano NPK were applied to the foliage of C. aromaticus, resulting in significant improvements in various growth traits and physiological parameters. These included enhanced photosynthetic efficiency, increased levels of photosynthetic pigments (chlorophyll a, chlorophyll b, and carotenoids), elevated nitrate reductase (NR) activity, accumulation of secondary metabolites, and increased essential oil (EO) content and yield. The optimum concentration of Nano NPK (6 g L−1) resulted in a 31.4 % increase in NR activity and 49.1 % and 51.7 % increases in total phenolic and flavonoid content, respectively, compared to the control plants. Furthermore, essential oil content and yield increased markedly by 140 % and 234 %, respectively, under this treatment, demonstrating that Nano NPK effectively stimulates secondary metabolism in medicinal plants. Overall, the findings indicate that foliar supplementation with Nano NPK fertilizer significantly enhances plant growth and physiological functions, while also offering a sustainable and efficient strategy to boost essential oil production in C. aromaticus, thereby increasing its commercial potential.